Investigating long-chain polyunsaturated fatty acid biosynthesis in teleost fish: Functional characterization of fatty acyl desaturase (Fads2) and Elovl5 elongase in the catadromous species, Japanese eel Anguilla japonica - Wang, Shuqi; Monroig, Oscar; Tang, Guoxia; Zhang, Liang; You, Cuihong; Tocher, Douglas R; Li, Yuanyou (Aquaculture, 2014)
The capacity for endogenous production of LC-PUFA from PUFA in euryhaline or diadromous fish is largely unknown other than for Atlantic salmon (Salmo salar), an anadromous species, which displays a freshwater pattern. The aim of the present study was to characterize the enzymes of the LC-PUFA pathway in Japanese eel (Anguilla japonica), the most important catadromous species currently being farmed. cDNAs of two key genes were cloned and functional assays showed they encoded a desaturase (Fads2) with D6 and D8 activity and an elongase (Elovl5) with activity towards C18 and C20 PUFA, with activities similar to marine fish and an D6/D8 activity ratio similar to Atlantic salmon. Furthermore, tissue distribution of the mRNA showed a clear marine pattern with highest expression in brain and eye. Phylogenetic analysis placed the eel cDNAs in line with classical taxonomy. The data suggest that diadromous species display a pattern of LC-PUFA biosynthesis capacity that likely reflects the environmental and nutritional influence of their early life stages rather than those of adult fish. Future studies aim to establish the full range of PUFA desaturases and elongases in Japanese eel and to provide further insight to the importance and relevance of LC-PUFA biosynthesis in fish species and the influence of diadromy.